First step banking in Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
A bank has been set up in the Masvingo province of Zimbabwe specifically for people who are poor. ZUBF is a local organization which provides, at preferential rates, credit to people who are a financial risk because they have no-one upon whom they...